Strategi Pembelajaran Guru Bahasa Arab dalam Meningkatkan Maharoh Kitabah Siswa Kelas Tahfidz MI Muhammadiyah 1 PK Sukoharjo - Putri, Fatimah Arisika; Abbas, Zainul; Qosim, Muhammad Nanang (MODELING: Jurnal Program Studi PGMI, 2024)
Education has an important position in human life. In the world of education there is a process of teaching and learning activities between an educator (teacher) and students. One of the successes of a teacher is to use learning strategies. From the statement above, the researcher analyzed the teacher's strategy and its application in improving speaking skills in the Arabic language material of the Tahfidz MI Muhammadiyah 1 PK Sukoharjo class. This study aims to find out and describe the strategies used by Arabic teachers in improving speaking skills in students of Tahfidz MI Muhammadiyah 1 PK Sukoharjo, as well as to determine the supporting and inhibiting factors of learning strategies in improving speaking skills. The research method used is qualitative method. This study used three data collection techniques, namely observation, interviews, and documentation. Researchers analyze the data using namely; data collection, data reduction, data presentation, and conclusions. While the data trianggulation used is a triangulation technique.